Ethnomathematics of sowing games in the southwest of the Indian Ocean - (:unkn) unknown (My University, 2017)
Sowing games are an abstract combinatorial game class. They are divided into two categories, the solo and the wari, the solo all located on the continental African territory in the south of the Sahara and in the southwest islands of the Indian Ocean closest to the continent.The rules of any abstract combinatorial game constitute an object of study, often neglected by ethnology, but which interests ethnomathematics, since it is algorithms, complex in the case of solo, implemented by non-specialists, and whose transmission is essentially oral.From the analysis of video recordings and ethnographic research carried out in our study area, we show that all the solo in our study area come from the Zanzibar bao, and that their rules become more and more simplified when We move away from this center, along the commercial roads and historical counters of this area.We also offer analysis tools to try to model and explain the speed and existence of apparently illegal blows of expert players.
Keywords: African Research